EXPLORING ENGINEERING EMPLOYABILITY COMPETENCY - Hasan, Hazmilah (Penerbit Universiti, Universiti Teknikal Malaysia Melaka, 2008)
The objectives of this study are to assess whether the suggested lack of interpersonal and enterprise skills competencies cause unemployment amongst engineering graduates in Malaysia, critically appraise if engineering undergraduates have received a quality work placement (appropriate to their learning, knowledge and employability skills) and to enhance interpersonal and enterprise skills competencies awareness amongst engineering undergraduates in Malaysia. This study employed mix-method survey and open-ended questionnaire. The survey result was analysed using the SPSS software package. The open ended data was interpreted. The qualitative result revealed that the students industrial training was the most valuable session to help them to be employed and they had received the appropriate task during the training.